A step forward for data protection and biomedical research - Dove, Edward S; Thompson, Beth; Knoppers, Bartha M (The Lancet (British edition), 2016)
To update previous correspondence to this journal,1 we are pleased to report that, in large part through the efforts of the biomedical research community, a European General Data Protection Regulation that is favourable for research was agreed by Member States and Parliament in December, 2015.2 Although the Regulation will probably not apply until mid-2018, now is an appropriate time to highlight the implications for biomedical research.